Examining the effect of personality on user acceptance of conditionally automated vehicles - S. Nordhoff; E. Lehtonen (Scientific Reports)
Abstract Automated vehicle acceptance (AVA) research has grown substantially in the past few years. There is a paucity of research on the role of the big five personality traits on attitudes towards automated vehicles (AVs) and AVA. This is a critical shortcoming given that personality is considered a critical factor explaining technology adoption. Our major theoretical contribution is the integration of the most popular personality measure – the big five – and one of the most influential technology acceptance models – Unified Theory of Acceptance and Use of Technology (UTAUT2). A questionnaire was administered to 9,339 respondents from nine countries to predict the behavioral intention to use conditionally automated vehicles (CondAVs). The original UTAUT2 was extended by trust and driver engagement and the big five personality traits openness, conscientiousness, extraversion, agreeableness, and neuroticism. Structural equation modeling was applied to examine the direct effects of these constructs on behavioral intention and the indirect effects of the personality traits on the independent constructs of the extended UTAUT2. The results have shown positive effects of social influence, trust, and performance expectancy on the behavioral intention to use CondAVs. Most of the hypotheses pertaining to the role of the personality traits on the UTAUT2 constructs were supported, but the effects were relatively small (< 0.25). Our findings support the usefulness of UTAUT2 in evaluating the success of AVs, providing crucial insights into the factors driving the acceptance of CondAVs. The cross-country analysis provides further insights into the role of an individual’s personality for AVA. Our study yields important implications for practitioners. Given the small effect sizes of personality, designing CondAVs around the personalities of their customers during development and commercialization may be ineffective to promote trust and acceptance.